Stewart's guide to employment law. 2nd ed. - Stewart, Andrew (Annandale, 2009)
"This new 2nd edition explains the Rudd Government's new Fair Work Act, which took effect on 1 July 2009. Subjects that are featured include the new National Employment Standards, the modern award system, the requirements of good faith bargaining, the role and functions of Fair Work Australia and the new unfair dismissal system."